1995
DOI: 10.1002/bjs.1800821033
|View full text |Cite
|
Sign up to set email alerts
|

Parastomal hernia: Local resiting and mesh repair

Abstract: A new approach for parastomal hernia repair is described that combines the simplicities of local surgery with the advantages of stomal resiting through a fresh area of the abdominal wall. Surgical technique, The stoma is mobilized about the mucocutaneous junction (Fig.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
3

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 2 publications
0
22
0
3
Order By: Relevance
“…Rubin et al 74 noted an incidence of 52 per cent for incisional hernia, whereas Cheung et al 46 reported an incidence of only 8 per cent. Stephenson and Phillips 78 suggested a local resiting though the abdominal wall fascia, with the addition of mesh to repair the defect at the previous stoma site. In this series three of eight patients had minor wound complications, none of which required removal of the mesh; there was no recurrence at a mean follow-up of 15 months.…”
Section: Repair By Stoma Relocationmentioning
confidence: 99%
“…Rubin et al 74 noted an incidence of 52 per cent for incisional hernia, whereas Cheung et al 46 reported an incidence of only 8 per cent. Stephenson and Phillips 78 suggested a local resiting though the abdominal wall fascia, with the addition of mesh to repair the defect at the previous stoma site. In this series three of eight patients had minor wound complications, none of which required removal of the mesh; there was no recurrence at a mean follow-up of 15 months.…”
Section: Repair By Stoma Relocationmentioning
confidence: 99%
“…This is not the case for the direct approach. The latter, in our estimation, must be accompanied by the insertion of a prosthesis whether it be polyester [Alexandre and Bouillot 1993, Leslie 1984, Stephenson 1995 as is our series, or polypropylene [Abdu 1982, Rosin andBonardi 1977]. In the absence of a prosthesis, recurrence rate can reach 75% [Rubin et al 1994].…”
Section: Discussionmentioning
confidence: 95%
“…A 2012 systematic review by Hansson et al deemed fascial repair outdated due to an overall morbidity rate of 22.6, 11.8 % surgical site infection and 69.4 % rate of recurrent PH [68]. Stoma relocation can result in recurrent PH in 0-76.2 % of patients [3,[64][65][66][69][70][71]. Stoma relocation can carry the added risk of a laparotomy and thus create three potential sites for hernia formation; however, in one series, 76 % of stoma relocation cases were successfully accomplished without a laparotomy [64].…”
Section: Operative Management Open Approachmentioning
confidence: 99%